Labor Market Distortions, Rural-Urban Inequality, and the Opening of People's Republic of China's Economy - Thomas Hertel; Fan Zhai (Asian Development Bank (ADB), 2004)
"This paper evaluates the impact of some key factor market reforms on ruralurban inequality and income distribution, using a household-disaggregated, recursive dynamic computable general equilibrium (CGE) model of People's Republic of China. It also explores how these factor market reforms interact with product market reforms currently under way as part of the country's WTO accession process. The simulation results show that reforms in the rural land rental market and hukou system, as well as increasing off-farm labor mobility, would reduce the urban-rural income ratio dramatically. Furthermore, the combination of WTO accession and factor market reforms improves both efficiency and equality significantly"
hdl:11540/1917
Keywords: 330; Ländlicher Arbeitsmarkt; Städtischer Arbeitsmarkt; Einkommensverteilung; Regionale Arbeitsmobilität; Arbeitsmarktpolitik; Reform; China